(untitled) (Fiep Bulletin - online, 2019)
The regulation of Physical Education as profession raised a reflection regarding to the necessity of professionaltraining of martial art coaches. The Jiu-Jitsu (JJ) is a martial art that has improved itself as combat sport, with increasing numberof its practitioners and strong connection with Brazilian people. The present study analyzed the process training of JJ coachtaking as reference both the "Craft Apprenticeship System" and the "Profession Concept" theoretical backgrounds. Thedocument analysis by means of Bardin’s Content Analysis Method was the research technique assumed to the data collectionand analysis. The documents analyzed were obtained from the website of the Confederação Brasileira de JJ (CBJJ), in 2016. Theresults showed that the training process of JJ coach has close similarity to the "Craft Apprenticeship System", presenting thefollowing aspects: I) The coaches essentially learn by doing; II) The “black belt” is the central person which is legally responsibleby their students; III) The JJ is represented by several institutions which have close similarities to the "Craft ApprenticeshipSystem"; IV) The CBJJ concedes to the coaches wide autonomy for the learning process; V) The learning activities are as if theywere secret practices. Based on these results, it is considered that both the discussion promoted by regulation of physicaleducation as profession, which called attention to the necessity of scientific background in the process training of sport coaches,and the sportivization and dissemination of the JJ were not able to stimulate the introduction of scientific knowledges in thetraining process of JJ coaches.